How do I solve the following functional equation: $$f(x)+12f^{-1}(x)=\frac{1}{x}f(x)$$ I've been doing a lot of functional equations, but I haven't done one yet that has the function and its inverse together. All I've done so far is figure out that $f(x)$ has a fixed point at $x=\frac{1}{13}$ and that $f(0)$ starts a cycle of orbit $2$.

Thanks! All help is appreciated!

  • 1
    $\begingroup$ Does $f$ need to have real domain and codomain? $\endgroup$ – orlp May 22 '17 at 13:39
  • 2
    $\begingroup$ You can trade the inverse function for a nesting with $$f(f^{-1}(x))=x=f\left(\frac{1-x}{12x}f(x)\right)$$ or $$f(f(x))+12x=\frac{f(f(x))}{f(x)}.$$ $\endgroup$ – Yves Daoust May 22 '17 at 15:44

We have

$$ y=f(x) $$


$$ x=f^{-1}(y)=g(y) $$


$$ (\frac{1}{x}-1)f(x)=12f^{-1}(x)\\ x=f(f^{-1}(x))=f(\frac{1}{12}(\frac{1}{x}-1)f(x))\\ $$

Thus, we can formulate a recursive numeric search on $f$:

$$ min_{df}\left|x-f\left(\frac{1}{12}(\frac{1}{x}-1)f(x)+df(x)\right)+df\left(\frac{1}{12}(\frac{1}{x}-1)f(x)\right)\right|\\ $$

  • $\begingroup$ What exactly is a recursive numeric search? $\endgroup$ – Franklin Pezzuti Dyer May 21 '17 at 21:31
  • $\begingroup$ I've been unable to make it converge though... Perhaps this problem dont have a clear solution, but also i was unable to prove that too. I discretized a vector $f$ over several testing range and applied a Newton Raphson gradient search over the function $f$ defined on that way, with different iterating rates, considering the indicated expression to be minimized for both the vector $x$, the current recursion for $f$ and the new step $df$ evaluated at the indicated function value. But i didnt have any results, yet. $\endgroup$ – Brethlosze May 21 '17 at 22:16

This is not a full answer but an alternate approach in addition to hypfco's. We have $y = f(x)$ and $x = f^{-1}(y)$.

Writing your equation as $(\frac{1}{x} - 1)f(x) = 12f^{-1}(x)$ we get

$$(\frac{1}{x} - 1)y = 12f^{-1}(f^{-1}(y))$$ $$(\frac{1}{f^{-1}(y)} - 1)y = 12f^{-1}(f^{-1}(y))$$ $$y = \frac{12}{\frac{1}{f^{-1}(y)} - 1}f^{-1}(f^{-1}(y))$$ $$y = -12\frac{f^{-1}(y)}{f^{-1}(y) - 1}f^{-1}(f^{-1}(y))$$

If we just write $g(x) = f^{-1}(x)$, we can solve the problem by finding a $g$ such that:

$$-12\frac{g(x)}{g(x)-1}g(g(x)) = x$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.